Application of electrical resistivity methods in quantitative assessment of groundwater reserve of unconfined aquifer - Ali Hago, Hago (2000)
The thesis describes the application of the electrical resistivity method in groundwater exploration carried out at Bukit Jalil-Serdang area, Selangor Darul Ehsan, Malaysia. Electrical Resistivity Imaging surveys have been conducted in order to locate, delineate subsurface water resources and estimate its reserve. A Wenner electrode configuration was employed. The field survey was conducted along thirteen profiles providing continuous coverage. Color-modulated sections of resistivity versus depth were plotted for all lines, giving an approximate image of the subsurface structure. The field survey was accompanied by a laboratory work. Resistivity of rock and soil samples taken from the field was measured and the resistivity formation factors were obtained. The porosity of the same sample was calculated. A relationship between the porosity and the formation factor has been established. The laboratory established relationship was applied to the data obtained in the field to calculate the porosity values of the formation present within the investigated area. The porosity values were contoured and plotted. Depth to the bedrock for each line was obtained. A 2-dimensional and 3-dimensional representation of the subsurface topography of the area was prepared using a commercial computer software. The use of the software also enabled the computation of groundwater reserve within the investigated area. The results showed that the layer associated with the aquifer has resistivities between 20 Q.m and 150 Q.m and is located at a depth varying from 5 to 20m. The layer has porosity between 18% and 35%. The results obtained from the electrical resistivity profiles indicate that the aquifer occupies a surface area of about 15977900 m² and has a mean depth of 13m, with net volume of 204610000 m³. The average aquifer porosity is 30%. Therefore, a usable capacity of about 61,383,000 ± 6,752,130 m³ can be inferred.